Contextualizing the social-ecological outcomes of coral reef fisheries management. (January 2020) - Johnson, Steven M.; Reyuw, Bertha M.; Yalon, Anthony; McLean, Matthew; Houk, Peter
Highlights: Integration of social and ecological data is fundamental for supporting resilience. Marine protected area success aligns with social system features. Gradient of human impacts structures non-protected fisheries. Community decision-making structure and fishing key for fisheries management. Abstract: Marine protected areas (MPAs) have emerged as a valuable tool in biodiversity conservation and fisheries management. However, the effective use of MPAs depends upon the successful integration of social and ecological information. We investigated relationships between the social system structure of coastal communities alongside biological data describing the status and trends in fish communities around Yap, Micronesia. Traditional marine tenure made Yap an ideal place to investigate the underlying principles of social-ecological systems, as communities own and manage spatially-defined coastal resources. Analysis of social survey data revealed three social regimes, which were linked to corresponding gradients of ecological outcomes. Communities with decentralized decision-making and a preference for communal forms of fishing had the greatest ecological outcomes, while communities lacking any form of leadership were linked to poor ecological outcomes. Interestingly, communities with strong top-down leadership were shown to have variable ecological outcomes, depending on the presence of key groups or individuals. We last investigated whether social perception could successfully predict the status of fish assemblages within non-managed reefs. Several biological metrics of fish assemblages within non-managed areas were significantly predicted by a gradient of human access, suggesting social perception could not predict the growing human footprint over the study period. These findings highlight the potentially overlooked role that community-oriented decision-making structures and fishing methods could play in successful conservation efforts, and the limitations of perception data. Policies that promote communal marine resource use offer a novel approach to improve fisheries management and promote social-ecological resilience.